PROBLEMATIKA IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN AQIDAH AHKLAK DI MADRASAH TSANAWIYAH AL-AZHAR KOTA PAGAR ALAM - Trapol, Fredi; Anggraini, Rita Yulia (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to identify and analyze the issues that arise in implementing the Independent Curriculum in the Aqidah Akhlak subject, from the perspectives of teachers, students, and the school environment. The research method used qualitative with a descriptive approach, collecting data through observation, interviews, and documentation, and analyzing it using data reduction, data presentation, and data verification techniques. The results show that the main obstacles lie in human resource readiness, limited teacher understanding of the new curriculum concept, adaptation of teaching materials relevant to aqidah and akhlak values during the learning process, and the lack of supporting facilities. In addition, differences in students’ backgrounds in terms of ability and understanding of religion also pose a challenge in applying varied learning models, requiring teachers to adjust the learning process to meet individual students’ needs. This study recommends enhancing teacher training, developing contextual learning modules, improving facilities to support the Independent Curriculum, and providing full support from educational institutions to ensure its successful implementation in the Aqidah Akhlak subject.